Early preclinical development of Mycobacterium tuberculosis amino acid biosynthesis pathway inhibitor DRILS-1398 as a potential anti-TB drug - Biswas, Deepesh; Edwin, Rebecca Kristina; Kumar, K. Shiva; Alam, Anwar; Kumar, Dhiraj; Chakraborty, Sandipan; Bulusu, Gopalakrishnan; Ahmad, Farhan Jalees; Shenoy, Gautham G.; Singh, Lakshyaveer; Agarwal, Mansi; Siraj, Fouzia; et al. (iScience, 2025)
The search for new anti-tubercular agents is vital for the fight against Mycobacterium tuberculosis, particularly given the rise of drug-resistant strains. DRILS-1398, a pyrazolo[4,3-d]pyrimidine derivative, was discovered as a potent inhibitor of M.tb chorismate mutase (M.tb-CM) with an IC50 = 3.0 ± 0.2 μM (n = 3) and IC90 = 10 μM. The compound demonstrated efficacy against multi-drug resistant M.tb strains (MIC = 4 μg/mL, ∼10.0 μM) and effective inhibition of intracellular M.tb in THP-1 macrophages. With favorable pharmacokinetics, moderate stability in vitro, and a promising safety profile, DRILS-1398 showed no toxicity at doses up to 500 mg/kg b.w./day when dosed orally daily once for 7 consecutive days in mice. Both DRILS-1398 and its formulation DRILS-1398(F) were successful in clearing M.tb infection from the lungs and spleen in murine models. These findings suggest DRILS-1398 as a promising lead candidate for developing a first-in-class anti-tubercular drug. [Display omitted] •DRILS-1398 is a 1st in class inhibitor of M.tb amino acid biosynthetic pathway•DRILS-1398 is effective against intracellular MDR-M.tb•Formulated DRILS-1398 elicits superior pharmacokinetics properties and efficacy•DRILS-1398 is safe, non-toxic, and well-tolerated in animal models Biological sciences; Medical Microbiology; Microbiology; Natural sciences; Pharmacology